Case Report of Vesiculobullous Impetigo - Ines Melania B Ola; Novia Yudhitiara; Hari Darmawan (STIKes Budi Luhur Cimahi, 2026)
Impetigo is a superficial bacterial skin infection commonly found in children, especially aged 2–5 years. This case report describes a 1 year 7 months old girl presenting with vesiculobullous lesions on the face and neck for one week, which ruptured and left yellowish crusts. The patient had previously received treatment from a primary health center without improvement. Clinical examination revealed multiple erythematous vesicles with crusting and well-defined borders on the face and neck. A diagnosis of vesiculobullous impetigo was established with differential diagnoses of contact dermatitis, staphylococcal scalded skin syndrome, and bullous pemphigoid. The patient was treated with gentamicin cream applied twice daily after bathing and oral amoxiclav syrup three times daily. Education on hygiene, infection prevention, and follow-up was also provided. Clinical improvement was evaluated after one week. Prognosis was good, both for life, function, and recovery. This case highlights the importance of accurate diagnosis and appropriate management in pediatric impetigo to prevent complications and transmission.